Analisis dan Perancangan Aplikasi Genggam Bumine di Bagian Pemerintahan Setda Kabupaten Banyuwangi - Iksir, Mariyam; Ghofur, Abd. (Jurnal Sistem Informasi Galuh, 2026)
Digital transformation in government has become an urgent necessity to deliver public services that are faster, more transparent, and more affordable. One of the most critical sectors is land information services, which often face problems such as limited data access, slow document verification, and the lack of integration between central and regional systems. This study aims to analyze the existing conditions and design a locally based land information system through the Genggam Bumine application developed at the Government Affairs Division of the Banyuwangi Regency Secretariat. The research method combines field research, library research, and a prototype approach to ensure that the system design aligns with user needs. The findings show that Genggam Bumine provides several key features, including land data request submission, certificate and parcel map search, document verification, and digital tracking of application status. The implementation of this application is expected to improve the efficiency and effectiveness of services, strengthen public transparency, and support the realization of the Banyuwangi Smart City program as well as the development of e-government at the regional level. Therefore, this research contributes to providing a practical solution for strengthening digital-based land services in local government.